THE IDENTIFICATION OF ABSORPTION LINES OF DYSPROSIUM IN THE SOLAR SPECTRUM. - Yushchenko, A. V.; Gopka, V. F. (Одеські астрономічні публікації, 2017)
12 additional absorption lines of Dy II were identified on the basis of calculations of synthetic spectrum and it’s comparison with the spectral atlas of solar flux.